Crisis-driven mobility between Ukraine and Poland: What does the available data (not) tell us - Ignacy Jóźwiak; Maria Piechowska (University of Warsaw, Centre of Migration Research (CMR), 2017)
The paper sheds light upon the arrivals of Ukrainians into Poland in the face of political, military and economic developments in Ukraine following the 2013/2014 Euromaidan events. The authors make use of the available primary and secondary sources to analyse Ukrainian labour and educational migration to Poland, shuttle trade and shopping tourism as well as asylum seeking. The recent development of these different forms of mobility from Ukraine to Poland against the backdrop of political crisis, armed conflict and economic recession in Ukraine can be reflected in the light of Ukraine's peripheral position and historically and politically shaped Polish-Ukrainian relations. The official statistics indicate a general increase in different forms of mobility between the two countries and, given the conflict-driven economic stagnation, the authors claim that further influx should be expected and Ukrainian migration is likely to become a consistent part of the Polish social landscape.
Keywords: 330; Ukraine; Poland; mobility; crisis; labour